Design and fabrication of hydrotalcite-like ternary NiMgAl layered double hydroxide nanosheets as battery-type electrodes for high-performance supercapacitors. Issue 17 (26th March 2019) - Jing, Chuan; Zhang, Qiang; Liu, Xiaoying; Chen, Yuxiang; Wang, Xin; Xia, Luhao; Zeng, Hao; Wang, Decai; Zhang, Wenzheng; Dong, Fan
Abstract : Hydrotalcite is an abundant mineral in nature and can be cost-effectively prepared in the laboratory, but there is almost no discussion about its application in the field of supercapacitors. Abstract : Hydrotalcite is an abundant mineral in nature and can be cost-effectively prepared in the laboratory, but there is almost no discussion about its application in the field of supercapacitors. Herein, hydrotalcite-like ternary NiMgAl LDHs with unique ultrathin nanosheets were designed and fabricated by a facile hydrothermal method. The preparation conditions, such as Ni/Mg molar ratio and hydrothermal reaction time, are evaluated carefully. The physical and chemical properties were also evaluated by various characterization techniques such as XRD, FIB/SEM, EDS, TEM, XPS and BET. The electrochemical behaviors of present samples were determined by CV, CC and cycling tests in a three-electrode system. As a battery-type electrode material in a supercapacitor, owing to the advantage of its unique layered structure, high specific area and obvious redox states, the fabricated Ni2 MgAl LDH-24 h nanosheets present an outstanding specific capacitance of 219.2 mA h g −1 at a current density of 1 A g −1 and superior cycling stability with 86.1% capacitance retention over 5000 cycles. Although 45.7% capacitance retention is not satisfactory when the current density increases from 1 to 3 A g −1 due to the NiMgAl LDH's low effective mass and conductivity, it is still a successful case for hydrotalcite application in supercapacitors by doping with Ni 2+ to achieve high electrochemical performance. The design and fabrication strategy can facilitate the application of the natural hydrotalcite mineral in the energy storage field.